The Correlation Between Angiotensin II Levels and Homeostatic Model Assessment of Insulin Resistance in Normotensive Young Adults with a Family History of Essential Hypertension - Stella Palar; Syarif Bakri; Haerani Rasyid; Idar Mappangara (Acta Medica Indonesiana)
Background: A family history of hypertension increases the risk of renin–angiotensin–aldosterone system activation, insulin resistance, and vascular inflammation, contributing to cardiovascular disease. Early vascular disturbances, marked by angiotensin II and insulin resistance assessed through the homeostatic model assessment of insulin resistance (HOMA-IR), play crucial roles in hypertension development. This study aims to determine the comparison and correlation between Ang II levels and HOMA-IR in normotensive young adults with or without offspring hypertension. Methods: We conducted this cross-sectional study by recruiting fifty normotensive participants, who were categorized into two groups: normotensive young adults who are offspring of parents with essential hypertension (case) and those who are not (control). The serum Ang II and HOMA-IR were measured. The comparative analysis was conducted using the Mann-Whitney test, and correlations were evaluated using Spearman’s test. Results: Among the 50 subjects (25 cases and 25 controls), a significant difference was observed in Ang II levels (p = 0.010), whereas HOMA-IR (p = 0.206) showed no notable difference between case and control. Notably, a positive correlation between Ang II and HOMA-IR (r = 0.554; p = 0.004) was observed in the case group, while the control group exhibited an insignificant correlation (r = –0.089; p = 0.671). Conclusion: There are marked differences in Ang II levels between normotensive young adults with a family history of essential hypertension and those without such history. Additionally, a significant correlation was found between Ang II and HOMA-IR in normotensive young adults who have a family history of essential hypertension.